To tweet or not to tweet about schizophrenia systematic reviews (TweetSz): study protocol for a randomised controlled trial - Jayaram, Mahesh; Bodart, Angelique Y.M.; Sampson, Stephanie; Zhao, Sai; Montgomery, Alan A.; Adams, Clive E. (BMJ Publishing Group Ltd, 2015)
Introduction: The Cochrane Schizophrenia Group (CSzG) has produced and maintained systematic reviews of effects of interventions for schizophrenia and related illness. Each review has a Plain Language Summary (PLS), for those without specialised knowledge, and an abstract, which are freely available from The Cochrane Library (https://summaries.cochrane.org). Increasingly, evidence is being distributed using social media such as Twitter and Weibo (in China) alongside traditional publications. Methods and analysis: In a prospective two-arm, parallel, open randomised controlled trial with a 1:1 allocation ratio, we will allocate 170 published systematic reviews into the intervention group (tweeting arm/Weibo arm) versus the control group (non-tweeting arm). Reviews will be stratified by baseline access activity, defined as high (≥19 views per week, n=14), medium (4.3 to 18.99 views per week, n=72) or low (<4.3 views per week, n=84), based on Google Analytics, which will also be used for evaluating outcomes. The intervention group will have three tweets daily using Hootsuite with a slightly different accompanying text (written by CEA and AB) and a shortened Uniform Resource Locator (URL) to the PLS: a) The review title as it appears in summaries.cochrane.org, b) A pertinent extract from results or discussion sections of the abstract and c) An intriguing question or pithy statement related to the evidence in the abstract. The primary outcome will be: total number of visits to a PLS in 7 days following the tweet. Secondary outcomes will include % new visits, bounce rate, pages per visit, visit duration, page views, unique page views, time on page, entrances, exiting behaviour and country distribution. Ethics and dissemination: This study does not involve living participants, and uses information available in the public domain. Participants are published systematic reviews, hence, no ethical approval is required. Dissemination will be via Twitter, Weibo and traditional academic means.